Key aspects for conception and construction of co-culture models of tumor-stroma interactions - Mason, James; Öhlund, Daniel (Frontiers in Bioengineering and Biotechnology, 2023)
The tumor microenvironment is crucial in the initiation and progression of cancers. The interplay between cancer cells and the surrounding stroma shapes the tumor biology and dictates the response to cancer therapies. Consequently, a better understanding of the interactions between cancer cells and different components of the tumor microenvironment will drive progress in developing novel, effective, treatment strategies. Co-cultures can be used to study various aspects of these interactions in detail. This includes studies of paracrine relationships between cancer cells and stromal cells such as fibroblasts, endothelial cells, and immune cells, as well as the influence of physical and mechanical interactions with the extracellular matrix of the tumor microenvironment. The development of novel co-culture models to study the tumor microenvironment has progressed rapidly over recent years. Many of these models have already been shown to be powerful tools for further understanding of the pathophysiological role of the stroma and provide mechanistic insights into tumor-stromal interactions. Here we give a structured overview of different co-culture models that have been established to study tumor-stromal interactions and what we have learnt from these models. We also introduce a set of guidelines for generating and reporting co-culture experiments to facilitate experimental robustness and reproducibility.